Big bodies, blurred lines: the impact of male body size on sensitivity to sexually dimorphic facial features - Zhu, Haoliang; Chen, Shitao; Lei, Xue; Ni, Zhe; Han, Chengyang (Frontiers in Psychology, 2025)
IntroductionSexual dimorphism plays an important role not only in gender perception but also in social judgment (e.g., dominance). Body size is a key indicator of men’s formidability, influencing their sensitivity to masculinity-based dominance toward other men. However, it remains unclear whether body size also affects men’s sensitivity to sexually dimorphic features in gender perception.Methods and resultsIn the current study, we found that men with larger body sizes—operationalized by height, weight, and BMI—exhibited reduced sensitivity to sexually dimorphic facial features during gender judgment. This finding suggests that individual differences (e.g., body size) can modulate men’s sensitivity to the perception of sexually dimorphic traits, potentially cascading into altered sensitivity to social judgments based on these features. In addition, the current study revealed that men showed greater sensitivity to sexually dimorphic features on male faces compared to female faces.DiscussionOverall, these findings contribute to the literature on individual differences in sensitivity to sexually dimorphic features and their implications for social judgment.